A control-oriented wave-excited linear model for offshore floating wind turbines. Issue 2 (September 2020) - Fontanella, A.; Al, M.; van der Hoek, D.; Liu, Y.; van Wingerden, J.W.; Belloli, M.
Abstract: The design of control strategies for floating offshore wind turbines (FOWTs) is even more difficult than for onshore and bottom-fixed offshore ones and a recognized control strategy for FOWTs is currently lacking. In order to design effective control strategies, the additional dynamics of these systems should be taken into account in the models used to solve this task. This paper presents the analytical derivation of a novel model conceived for control design purposes. In detail, the model is based on a linear description of the highly non-linear phenomena that are relevant for an FOWT. The quasi-steady assumption is used to give a description of the aerodynamic loads and how these are influenced by the main control inputs. Hydrodynamic radiation and diffraction forces are introduced by means of linear-time-invariant parametric models. Simulation results shows that the proposed linear model is able to predict the structural response of the turbine system and the floating platform effectively in the case of control inputs, wind and wave disturbances. Compared to the nonlinear high-fidelity model, the proposed model shows similar results, however, without much complexity, which is promising in the desing of FOWT control strategies.